Cloud`s SaaS Security by Biometric Concept - Singh, Dharamjeet; Shukla, Surabhi (International Journal of Computer Sciences and Engineering, 2014)
Personal privacy is of utmost importance in the global networked world. Some vital information that are disseminated within an office, across offices ,between branches, of an organization and other external bodies and establishments at times get into the hands of the unauthorized persons who may tamper with that contents of the information. And if no security measures are taken, there is no doubt that such data and other sensitive information will be exposed to threats such as impersonation, in-secrecy, corruption, repudiation, break-in or denial of services that may cause serious danger on the individual or organization. A secure system should maintain the integrity, availability, and privacy of data. Data integrity usually means protection from unauthorized modification, resistance to penetration and protection from undetected modification.